Carlo Pini (1806-1879). Conservatore, fotografo, editore - Naldi, Chiara (Rivista di studi di fotografia. Journal of Studies in Photography, 2016)
Based on unpublished sources, this article charts the significant photographic production of Carlo Pini, previously characterised as a mere amateur by photo-historian Piero Becchetti. Beginning in the late 1860s, Pini promoted and conducted photographic campaigns on ancient drawings and ‘grottesche’ decorations in the Uffizi Gallery, as well as on artists’ autographed manuscripts in the Archivio di Stato in Florence. Pini’s photographic reproductions were offered to a variety of potential users, including artists, scholars, and archivists. He was also an prolific publisher whose business, located in the heart of Florence, was aimed at an international public.